An interpretative framework for analysing managerial ideology, normative control, organizational culture and the self - Theaanna Kiaos (Cogent Business & Management, 2023)
This article presents an interpretative framework that fuses together key concepts that would be applied by way of ethnographic and qualitative research methods. The framework seeks to enable interpretations concerning the subjective experience of employees under various cultural conditions by specifying essential conceptual building blocks that gradually build on top of each other, resulting in a more complete theoretical framework for empirical application. The framework is highlighted in four parts A, B, C and D to enable an analysis of an organization's managerial ideology, normative control, an organization's culture from the integrationist perspective, its various subcultures and microcultures from the differentiation perspective, and cultural ambiguity from the fragmentation perspective. In addition, interpretations concerning the performances displayed by employees are supported by adopting one of the six sites of enactment as a guide for dramaturgical interpretation, notably, front stage scenes, front stage encounters, front stage relationships, back stage scenes, back stage encounters and back stage relationships. Finally, the interpretative framework enables the analysis of subjective experiences by adopting psychological and sociological concepts of the self as employees traverse various cultural conditions. This article extends existing theory by expanding the realm of possible interpretations concerning the subjective experiences of employees under various cultural conditions within organizational settings.
Keywords: 650; cultural psychology; dramaturgy; ethnography; managerial ideology; normative control; organizational culture; presentation ritual; qualitative methods; sites of enactment